2017
DOI: 10.18697/ajfand.79.16510
|View full text |Cite
|
Sign up to set email alerts
|

Dietary calcium intake and sunlight exposure among children aged 6-23 months in Dale Woreda, Southern Ethiopia

Abstract: Nutritional rickets can be caused by either or both calcium and vitamin D deficiencies, and can frequently occur in Africa. In Ethiopia, limited evidence exists regarding the calcium intake of children and their sunlight exposure practices. The purpose of this study was to assess information regarding dietary calcium intake and sunlight exposure practice, which are factors related to nutritional rickets. The study was conducted in Dale Woreda, Southern Ethiopia using a community based cross-sectional survey de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
(13 reference statements)
0
10
2
Order By: Relevance
“…This finding was slightly lower than the study done at Debre Markos on exposing without sun screening and time of exposure which accounts 57.3% and 99.1%, respectively; whereas, its higher on duration of exposure which accounts 25.5% [19]. This study finding was also incomparable with similar study done in Dale woreda of Southern Ethiopia as shown that 41.1% of the mothers exposed their child to sunlight within 1 month of birth [24].…”
Section: Discussioncontrasting
confidence: 64%
“…This finding was slightly lower than the study done at Debre Markos on exposing without sun screening and time of exposure which accounts 57.3% and 99.1%, respectively; whereas, its higher on duration of exposure which accounts 25.5% [19]. This study finding was also incomparable with similar study done in Dale woreda of Southern Ethiopia as shown that 41.1% of the mothers exposed their child to sunlight within 1 month of birth [24].…”
Section: Discussioncontrasting
confidence: 64%
“… 22 However, the finding was inconsistent with the reports of other studies, such as 67.6% in Aleta Wondo, 21 40% in Gondar, 23 and 49.4% in Southern Ethiopia. 27 Regarding the time of exposure, majority (83%) of mothers exposed their babies to sunlight between 8:00 and 10:00 AM. However, different studies reported variable rates about the exposure of infants to sunlight in the depicted period: e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Though it was not a major objective of all surveys conducted, some studies (Tezera et al, 2015;Regassa, 2014;Negash et al, 2014;Ersino et al, 2013), collected and analyzed wealth and food security status of the households surveyed. Household food security was measured by using tools developed by the Food and Nutrition Technical Assistance Project (FANTA).…”
Section: Household Wealth and Food Security Statusmentioning
confidence: 99%